2016
DOI: 10.1037/xhp0000269
|View full text |Cite
|
Sign up to set email alerts
|

Eye movement evidence for an immediate Ganong effect.

Abstract: Listeners tend to categorize an ambiguous speech sound so that it forms a word with its context (Ganong, 1980). This effect could reflect feedback from the lexicon to phonemic activation (McClelland & Elman, 1986), or the operation of a task-specific phonemic decision system (Norris, McQueen, & Cutler, 2000). Because the former account involves feedback between lexical and phonemic levels, it predicts that the lexicon's influence on phonemic decisions should be delayed and should gradually increase in strength… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
33
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(39 citation statements)
references
References 49 publications
(77 reference statements)
3
33
0
Order By: Relevance
“…However, they investigated the much easier s/f contrast, and in word-final fricatives, where the vocoid is heard before the fricative, and no more information arrive after it (lessening the need for a buffer). More important, Kingston et al (2016) showed what appears to be immediate use of frication spectra for word initial fricatives. This study, which was published after we completed data collection for this project, also examined the s/f distinction.…”
Section: Fricativesmentioning
confidence: 95%
See 4 more Smart Citations
“…However, they investigated the much easier s/f contrast, and in word-final fricatives, where the vocoid is heard before the fricative, and no more information arrive after it (lessening the need for a buffer). More important, Kingston et al (2016) showed what appears to be immediate use of frication spectra for word initial fricatives. This study, which was published after we completed data collection for this project, also examined the s/f distinction.…”
Section: Fricativesmentioning
confidence: 95%
“…However, as we argued in Experiment 4, listeners may be capable of making a decision when forced to, even if they do not do so in uninterrupted processing. A more serious discrepancy arises from Kingston et al (2016), who show some evidence of early use of frication in the /s/ vs. /f/ contrast. However, they did not perform the kind of analysis needed to compare the use of frication to other cues, and there are numerous methodological issues that undercut the ability of this study to support immediate integration.…”
Section: Limitationsmentioning
confidence: 99%
See 3 more Smart Citations